#### Linear number patterns or arithmetic sequences : answers.

1.1
8;   13;   18;   . . .
1.2
38;   53;   68;   . . .
a = 8  and  d = 13 − 8   =   5
a = 38  and  d = 53 − 38   =   15
Next two terms T2 = 18 + 5 = 23
Next two terms T2 = 68 + 15 = 83
T3 = 23 + 5 = 28
T3 = 83 + 15 = 98
Tn = a + (n − 1)d
Tn = a + (n − 1)d
= 8 + (n − 1)(5)
= 38 + (n − 1)(15)
= 8 + 5n − 5
= 38 + 15n − 15
= 5n + 3
= 15n + 23
1.3
−23;   −15;   −7;   . . .
1.4
54;   41;   28;   . . .
a = −23  and  d = −15 −(− 23)   =   8
a = 54  and  d = 41 − 54   =  − 13
Next two terms T2 = −7 + 8 = 1
Next two terms T2 = 28 + (−13) = 15
T3 = 1 + 8 = 9
T3 = 15 + (−13) = 2
Tn = a + (n − 1)d
Tn = a + (n − 1)d
= −23 + (n − 1)(8)
= 54 + (n − 1)(−13)
= 8n − 31
= 67 − 13n
2.1
a = 7   and    d   = 16− 7  = 9
2.2
a = 7   and    d   = 16− 7  = 9
Tn = a + (n − 1)d
Tn = a + (n − 1)d
= 7 + (n − 1)(9)
7 + (n − 1)(9)  =  124
= 7 + 90
9n − 2  =  124
= 97
9n  =  126
n  =  14
3.1
42  − 35 = 7 and 35 − 28 = 7
This is a linear number pattern because each term is equal to its predeccessor plus 7.
3.2
a = 28   and    d   = 7
3.3
Tn = a + (n − 1)d
Tn = a + (n − 1)d
Tn = 203 :   28 + (n − 1)(7)  =  203
T18 = 28 + (18 − 1)(7)
28 + 7n − 7  =  203
= 28 + 119
7n  =  182
= 147
n  =  26
4.1
a = 18   and    d   = 9
Tn = a + (n − 1)d
= 18 + (n − 1)(9)
= 9n +  9
4.2
Tn = a + (n − 1)d
OR
Tn = 9n +  9
T23 = 18 + (23 − 1)(9)
T23 = 9(23) +  9
= 18 + 198
=  207 +  9
= 216
= 216
4.3
Tn = a + (n − 1)d
OR
Tn = 9n +  9
Tn = 288:  18 + (n − 1)(9) = 288
Tn = 288:  9n +  9 =  288
18 + 9n − 9  = 288
9n +  9 = 288
9n +  9  = 288
9n = 288 − 9
n = 31
n = 31
4.4
Tn = a + (n − 1)d < 165
OR
Tn = 9n +  9 < 165
18 + (n − 1)(9) < 165
9n +  9 <  165
18 + 9n − 9  < 165
9n < 165 − 9
9n +  9  < 165
9n < 156
n < 17,333...
n < 17,333...
n = 17
n = 17
5.1
a = 53   and    d   = −5
5.2
Tn = a + (n − 1)d
Tn = a + (n − 1)d
Tn = −27 :   53 + (n − 1)(−5)  = − 27
T7 = 53 + (7 − 1)(−5)
53 −5n  + 5  = − 27
= 53 + (−30)
−5n  = −85
= 23
n  =  16
6.1
a = 63   and    d   = −8
6.2
Tn = a + (n − 1)d
Tn = a + (n − 1)d
T7 = 63 + (7 − 1)(−8)
= 63 + (n − 1)(−8)
= 63 − 48
= 71 − 8n
= 15
6.3
Tn = −25 : 63 + (n − 1)(−8) = − 25
6.4
Tn > 0 :   71  − 8n > 0
63 − 8n + 8 = − 25
− 8n > −71
− 8n = − 96
<  8,875
n = 12
n =  8
7.1
a = − 35   and    d   = 7
7.2
T18 =  −35  + (18 − 1)(7)
Tn = a + (n − 1)d
=  −35  + 119
= −35  + (n − 1)(7)
=  84
= −35  + 7n − 7
7.3
Tn =  35 :   7n − 42 = 35
=  7n − 42
7n = 77
n = 11
7.4
Tn >  110 :   a + (n - 1)d > 110
7.5
Tn <  180 :   7n − 42 < 180
−35 + (n − 1)(7) > 110
7n <  180 + 42
−35 + 7n − 7 > 110
7n < 222
7n  > 152
n < 31,714..
n  > 21,71
n = 31
n  =  22
8.1
a = 87  and d = − 9
8.2
Tn =  15 :   a + (n - 1)d = 15
Tn =  a + (n - 1)d
87  +  (n − 1)(−9) = 15
T13 = 87 + (13 − 1)(−9)
87 − 9n + 9  =  15
= 87 − 108
− 9n  =  15 − 96
= − 21
n  = 9
8.3
Tn < − 60 :   a + (n - 1)d < − 60
8.4
Tn >  − 94 :   a + (n - 1)d > − 94
87 + (n - 1)(−9) < − 60
87  +  (n - 1)(−9) > − 94
87 − 9n + 9 < − 60
87 − 9n + 9 > − 94
− 9n < − 60 − 96
− 9n > − 94 − 96
− 9n < − 156
− 9n > − 190
> 17,33....
< 21,111....
n = 17
n = 21
8.5
Tn < 0 :   a + (n - 1)d < 0
87 + (n - 1)(−9) < 0
− 9n < − 96
> 10,666....
n = 11
9.
T10 = 44 :   a + (10 - 1)d = 44
AND
T19 = 80 :   a + (19 - 1)d = 80
a + 9d = 44   . . . (1)
a + 18d = 80   . . . (2)
a + 18d = 80   . . . (2)
(2) − (1) :
9d = 36
d = 4
Into (1) :
a + 9(4) = 44
a = 8
T1 = 8;   T2 = 8 + 4 = 12;    T3 = 12 + 4 = 16;
10.
T9 = 32 :   a + (9 - 1)d = 32
AND
T14 = 47 :   a + (14 - 1)d = 47
a + 8d = 32   . . . (1)
a + 13d = 47   . . . (2)
a + 13d = 47   . . . (2)
(2) − (1) :
5d = 15
d = 3
Into (1) :
a + 8(3) = 32
a = 8
T1 = 8;   T2 = 8 + 3 = 11;    T3 = 11 + 3 = 14;
11.
T5 = 5 :   a + (5 - 1)d = 5
AND
T12 = − 9 :   a + (12 - 1)d = − 9
a + 4d = 5   . . . (1)
a + 11d = − 9   . . . (2)
a + 11d = − 9   . . . (2)
(2) − (1) :
7d = − 14
d = − 2
Into (1) :
a + 4(− 2) = 5
a = 13
T1 = 13;   T2 = 8 + (− 2) = 11;    T3 = 11 + (− 2) = 9;
12.
T6 = − 26 :   a + (6 - 1)d = − 26
AND
T15 = − 53 :   a + (15 - 1)d = − 53
a + 5d = − 26   . . . (1)
a + 14d = − 53   . . . (2)
a + 14d = − 53   . . . (2)
(2) − (1) :
9d = − 27
d = − 3
Into (1) :
a + 5(− 3) = − 26
a = − 11
T1 = − 11;   T2 = − 11 + (− 3) = − 14;    T3 = − 14 + (− 3) = − 17;
13.
T6 = 27 :   a + (6 - 1)d = 27
AND
T11 = 47 :   a + (11 - 1)d = 47
a + 5d = 27   . . . (1)
a + 10d = 47   . . . (2)
a + 10d = 47   . . . (2)
(2) − (1) :
5d = 20
d = 4
Into (1) :
a + 5(4) = 27
a = 7
13.1
T15  =  a + (n - 1)d
13.2
Tn =  87 :   a + (n - 1)d = 87
=  7 + (15 - 1)(4)
7 + (n - 1)(4) = 87
=  7 + 56
4n + 3 = 87
= 63
n = 21
14.
T9 = T5 + 12  :   a + (9 - 1)d = a + (5 - 1)d + 12
a + 8d = a + 4d + 12
4d = 12
d = 3
T24 = 74  :   a + (24 - 1)(3) = 74
a = 5
T1 = 5;   T2 = 5 + 3 = 8;    T3 = 8 + 3 = 11;
15.
T21 = T6 + 30  :   a + (21 - 1)d = a + (6 - 1)d + 30
a + 20d = a + 5d + 12
15d = 30
d = 2
T13 = 33  :   a + (13 - 1)(2) = 33
a = 9
15.1
T10  =  a + (n - 1)d
15.2
Tn =  67 :   a + (n - 1)d = 67
=  9 + (10 - 1)(2)
9 + (n - 1)(2) = 67
=  9 + 18
2n = 60
= 27
n = 30
16.
d = T3 − T2 = T2 − T1   :  (2x − 1) −(x + 2) = (x + 2) − (x − 2)
2x − 1 −x − 2 = x + 2 − x + 2
x − 3 = 4
x = 7
T1 = 7 − 2 = 5;     T2 = 7 + 2 = 9;     T3 = 2(7) − 1 = 13;
17.1
d = T3 − T2 = T2 − T1   :  (4x + 6) − (5x  +  5) = (5x + 5) − (7x  −  4)
4x + 6 − 5x − 5 = 5x + 5 − 7x + 4
− x  + 1 = − 2x + 9
x = 8
T1 = 7(8) − 4 = 52;     T2 = 5(8) + 5 = 45;     T3 = 4(8) + 6 = 38;
a = 52  and  d = 45 − 52 = −7
17.2
T6  =  a + (n - 1)d
17.3
Tn < 2 :   a + (n - 1)d < 2
=  52 + (6 - 1)(−7)
52 + (n - 1)(−7) < 67
=  52  − 35
− 7n < − 57
= 17
> 8,14..
n = 9
18.1
d = T3 − T2 = T2 − T1   :  (5x − 3) − (3x) = (3x) − (2x  − 2)
5x − 3 − 3x = 3x − 2x + 2
2x − 3 = x + 2
x = 5
T1 = 2(5) − 2 = 8;     T2 = 3(5) = 15;     T3 = 5(5) − 3 = 22;
a = 8  and  d = 15 − 8 = 7
18.2
T8  =  a + (n - 1)d
18.3
Tn > 100 :   a + (n - 1)d > 100
=  8 + (8 - 1)(7)
8 + (n - 1)(7) > 100
=  8  + 49
7n > 100− 1
= 57
n > 14,14..
n = 15